Research on Three-dimensional Tracking Technology of Aviation Plugs and Design of Auxiliary Soldering Systems - Jiao, Wei; Du, Wangjue (International Journal of Computer Science and Information Technology, 2025)
Aviation plugs are characterized by safety, reliability, waterproof and dustproof, and have been widely used in various industries. Aviation plugs are mainly welded manually at present, and this method has low welding efficiency and high error rate. Three-dimensional tracking technology of aviation plug is the key to the realization of aviation plug auxiliary welding system, this paper proposes an improved three-dimensional tracking method based on the vision SLAM framework: the position estimation method based on the fusion of the direct method and the CMT feature point method, and the fast closed-loop detection method based on the model of the back-end. On this basis, the development of the aviation plug assisted welding system was launched, and finally experimental validation was carried out on a self-made dataset to test and evaluate the system functions. The results show that the aviation plug auxiliary welding system can, to a certain extent, solve the various problems occurring in manual welding, and has certain research significance in improving both welding accuracy and welding efficiency.